2019
DOI: 10.1159/000499376
|View full text |Cite
|
Sign up to set email alerts
|

Temporary Filtering Bleb Failure Induced by Anterior Chamber Sulfur Hexafluoride Gas: A Complication after Descemet Membrane Endothelial Keratoplasty

Abstract: Herein, we report two clinical cases with acute temporary filtering bleb obstruction by gas tamponade after Descemet membrane endothelial keratoplasty (DMEK) surgery and postoperative intraocular pressure (IOP) peaks. Both patients underwent uncomplicated DMEK surgery with 20% sulfur hexafluoride (SF6) anterior chamber tamponade and had previous trabeculectomy for glaucoma. Prior to surgery, both patients showed patent bleb function with low to normal IOP without antiglaucomatous medication. After u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Although previous studies found no evidence that the choice of endotamponade [20% sulfur hexafluoride (20% SF6) or air] has an impact on IOP after DMEK, [12][13][14][15][16] a variety of other patientrelated and surgery-related factors such as previous surgery and preoperatively elevated IOP seem to play a role. [17][18][19] Early detection and immediate treatment are crucial to avoid ocular damage including Urrets-Zavalia syndrome. In general, high IOP like in primary angle-closure glaucoma may cause significant changes in corneal endothelial cell count (ECC), central corneal thickness (CCT), and visual acuity.…”
mentioning
confidence: 99%
“…Although previous studies found no evidence that the choice of endotamponade [20% sulfur hexafluoride (20% SF6) or air] has an impact on IOP after DMEK, [12][13][14][15][16] a variety of other patientrelated and surgery-related factors such as previous surgery and preoperatively elevated IOP seem to play a role. [17][18][19] Early detection and immediate treatment are crucial to avoid ocular damage including Urrets-Zavalia syndrome. In general, high IOP like in primary angle-closure glaucoma may cause significant changes in corneal endothelial cell count (ECC), central corneal thickness (CCT), and visual acuity.…”
mentioning
confidence: 99%
“…DMEK in glaucomatous eyes with previous glaucoma surgery is frequently challenging due to progressed corneal edema, anatomical alterations of the anterior chamber-like anterior synechiae, tube endings from glaucoma drainage devices (GDD), or large iridectomies after trabeculectomy. This can complicate unfolding of the graft or lead to an accelerated postoperative loss of gas from the anterior chamber resulting in an increased risk of graft detachment [11][12][13]. The rate of graft failure in eyes with preexisting glaucoma and after glaucoma surgery is reported to be increased [14,15].…”
Section: Key Messagesmentioning
confidence: 99%